Finding refuge : real-life immigration stories from young people - Rouse, Victorya (Zest Books, 2021)
"What is a refugee? English teacher Victorya Rouse assembles a collection of true teen immigration stories essential for our times, complete with maps, context, and background on the refugees' home countries"--